Engineered Bacillus subtilis for the de novo production of 2′-fucosyllactose - Quanwei Zhang; Zhenmin Liu; Hongzhi Xia; Ziyang Huang; Yonglian Zhu; Linfeng Xu; Yanfeng Liu; Jianghua Li; Guocheng Du; Xueqin Lv; Long Liu (Microbial Cell Factories, 2022)
Abstract Background The most abundant human milk oligosaccharide in breast milk, 2′-fucosyllactose (2′-FL), has been approved as an additive to infant formula due to its multifarious nutraceutical and pharmaceutical functions in promoting neonate health. However, the low efficiency of de novo synthesis limits the cost-efficient bioproduction of 2′-FL. Results This study achieved 2′-FL de novo synthesis in a generally recognized as safe (GRAS) strain Bacillus subtilis. First, a de novo biosynthetic pathway for 2′-FL was introduced by expressing the manB, manC, gmd, wcaG, and futC genes from Escherichia coli and Helicobacter pylori in B. subtilis, resulting in 2′-FL production of 1.12 g/L. Subsequently, a 2′-FL titer of 2.57 g/L was obtained by reducing the competitive lactose consumption, increasing the regeneration of the cofactor guanosine-5′-triphosphate (GTP), and enhancing the supply of the precursor mannose-6-phosphate (M6P). By replacing the native promoter of endogenous manA gene (encoding M6P isomerase) with a constitutive promoter P7, the 2′-FL titer in shake flask reached 18.27 g/L. The finally engineered strain BS21 could produce 88.3 g/L 2′-FL with a yield of 0.61 g/g lactose in a 3-L bioreactor, without the addition of antibiotics and chemical inducers. Conclusions The efficient de novo synthesis of 2′-FL can be achieved by the engineered B. subtilis, paving the way for the large-scale bioproduction of 2′-FL titer in the future.